Trio - Gesellschaftswissenschaften - Barth, Wera; Brammer, Tatjana; Grunemann, Vera; Lücke, Martin; Muttu, Cihon; Pankratz, Wolfgang; Schuster, Heike (Westermann, 2024)
Leben in der Altsteinzeit.- Vorgeschichte.- Frühgeschichte.- Antike.- Mittelalter.- Neuzeit